Periodisasi Dan Transformasi Seni Ukir Jepara: Negosiasi Bentuk, Fungsi, Dan Makna Dalam Konteks Global - Agus Setiawan (Universitas Dian Nuswantoro, 2026)
Jepara wood carving is an Indonesian cultural heritage shaped through historical, social, economic, and political interactions from the Kalingga Kingdom era to contemporary globalization. This study examines the periodization and transformation of form, function, and meaning in Jepara wood carving as an ongoing negotiation between local tradition and modern demands. Employing a historical-descriptive approach based on literature review and visual documentation, the study identifies four key periods: an early kingdom period in which carving served as a symbolic-religious medium; a colonial and Kartini period marking the transition toward commodification; an industrial period driving production expansion and motif standardization; and a contemporary period characterized by design simplification under global market pressure. Findings indicate that the persistence of Jepara wood carving lies not in formal stability but in its adaptive capacity to shifting socio-economic contexts, while its meaning has shifted from cosmological symbolism toward visual identity and a city-branding instrument. These findings underscore that safeguarding Jepara wood carving requires an integrated strategy combining design innovation, vocational education, and history-based cultural policy. The study offers an original contribution through a form-function-meaning negotiation framework for periodization, enriching heritage sustainability and city branding scholarship within traditional craft-based creative industries.